(untitled) (SIRJANĀ – A Journal Of Arts and Art Education, 2019)
Sacred Prayer Flags of different colours and symbols are not just decorative pieces. Symbols have more deeper meaning and the attached intangible beliefs than their mere outer creativity. Each and every colour and objects symbolizes good fortune, health, happiness, protection. The prayer flags are very sacred, because they contain texts from the holy sutras termed as ’mantras’ and symbols that should be respected. Hence the painted or printed objects and colours are of great values to humanity.